Reuse of Retired Wind Turbine Blades in Civil Engineering - Xuemei Yu; Changbao Zhang; Jing Li; Xue Bai; Lilin Yang; Jihao Han; Guoxiang Zhou (Buildings)
The rapid growth of the wind energy sector has led to a rising number of retired wind turbine blades (RWTBs) globally, posing significant environmental and logistical challenges for sustainable waste management. Handling enormous RWTBs at their end of life (EoL) has a significant negative impact on resource conservation and the environment. Conventional disposal methods, such as landfilling and incineration, raise environmental concerns due to the non-recyclable composite material used in blade manufacturing. This study explores the upcycling potential of RWTBs as innovative construction materials, addressing both waste reduction and resource efficiency in the construction industry. By exploring recent advancements in recycling techniques, this research highlights applications such as structural components, lightweight aggregates for concrete, and reinforcement elements in asphalt pavements. The key findings demonstrate that repurposing blade-derived materials not only reduces landfill dependency but also lowers carbon emissions associated with conventional construction practices. However, challenges including material compatibility, economic feasibility, and standardization require further investigation. This study concludes that upcycling wind turbine blades into construction materials offers a promising pathway toward circular economy goals. To improve technical methods and policy support for large-scale implementation, it recommends collaboration among different fields, such as those related to cementitious and asphalt materials.